Reducing Nitrate and Phosphate Concentrations in Shrimp Wastewater Aquaculture Using Gelidium corneum - Indraswari, Nabila; Adharini, Ratih Ida (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
Shrimp culture wastewater contains residual feed and shrimp metabolism. Shrimp wastewater if not managed prop-erly will be harmful to the long term viability of the farming itself and threatens environmental sustainability. This study aims to determine the potential and effectiveness of Gelidium corneum with different densities as a biofilter for vaname shrimp culture waste. This study used a completely randomized design method consisting of 3 treatments and 3 replications using different density treatments, namely T1 (1 gL-1); T2 (2 gL-1); and T3 (3 gL-1) in an aquarium volume of 30 L. The parameters observed included the concentration of nitrate, phosphate, temperature, TDS, TSS, salinity, DO, pH. Absorption effectiveness and growth of G. corneum were measured at the beginning and end of the study. G. corneum is able to reduce the concentration of phosphate in water is higher than lowering the content of nitrate. G. corneum with a density of 1 gL-1 showed the best performance in absorbing nitrate by 8 on day 15. While the 2 gL-1 treatment was able to reduce the phosphate concentration by 92 in 25 days. Absorption of Total Nitrogen content in the thallus obtained in the treatment of 2 gL-1 was 32 and total phosphate was 58 for 25 days. Therefore G. corneum can be used as a candidate for commodity in Integrated Multi Trophic Aquaculture (IMTA). © 2022, Polskie Towarzystwo Inzynierii Ekologicznej (PTIE). All rights reserved.